Bringing Vygotskian Approach into Early Childhood Education in Indonesia: Empowering the Daycare - Rahardjo, Maria Melita (Universitas Negeri Semarang, 2016)
Studies and researches revealed the importance of early childhood education. Many theories of early human development have been developed and employed to provide better educational system in those early years. One of the prominent theories comes from Lev S. Vygotsky’s work. His theory, which is also known as the sociocultural theory, introduces several powerful ideas for understanding and facilitating young children’s development and learning. This paper will examine some of the ideas that have significant impacts on the early childhood educational system. Afterward, the paper will briefly explain about the early childhood system in Indonesia at the present time, including: (1) Short of the government policies and goals; (2) The type of early childhood services; and (3) The new curriculum (known as kurikulum 2013). Based on the examination, it will be evident that the Vygotskian perspectives are basically in accordance with the government’s vision. Furthermore, after examining the early childhood system in Indonesia, I suggest that daycare is the most appropriate form of early childhood services for promoting the Vygotskian approach, which will benefit most of the children